Turn-taking: a case study of early gesture and word use in answering WHERE and WHICH questions - Clark, Eve V.; Lindsey, Kate L. (Frontiers in Psychology, 2015)
When young children answer questions, they do so more slowly than adults and appear to have difficulty finding the appropriate words. Because children leave gaps before they respond, it is possible that they could answer faster with gestures than with words. In this case study of one child from age 1;4 to 3;5, we compare gestural and verbal responses to adult Where and Which questions, which can be answered with gestures and/or words. After extracting all adult Where and Which questions and child answers from longitudinal videotaped sessions, we examined the timing from the end of each question to the start of the response, and compared the timing for gestures and words. Child responses could take the form of a gesture or word(s); the latter could be words repeated from the adult question or new words retrieved by the child. Or responses could be complex: a gesture + word repeat, gesture + new word, or word repeat + new word. Gestures were the fastest overall, followed successively by word-repeats, then new-word responses. This ordering, with gestures ahead of words, suggests that the child knows what to answer but needs more time to retrieve any relevant words. In short, word retrieval and articulation appear to be bottlenecks in the timing of responses: both add to the planning required in answering a question.